1955
DOI: 10.1139/b55-003
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study of Chromosome Behavior in a Wheat Haploid

Abstract: Bivalents, univalents, end-to-end and side-by-side associations, also chromosome distributions to the poles were associatively recorded for each of approximately 2000 meta-anaphase cells of a haploid Triticum aestivum L. It was demonstrated that the distribution of the univalents to the polar groups was not random. An inverse relationship between side-by-side association and bivalent frequencies was also demonstrated, and this formed the first in a series of analytical steps which led to a description of chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

1958
1958
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 1 publication
1
36
1
Order By: Relevance
“…However, chromosomes which have paired at prophase without chiasmaformation sometimes remain secondarily associated as univalents (Person, 1955 Riley and Chapman, 1957). Occasionally the secondarily associated univalents then orientate on the first metaphase plate and separate one to each pole in late anaphase.…”
Section: Meiotic Behaviourmentioning
confidence: 99%
“…However, chromosomes which have paired at prophase without chiasmaformation sometimes remain secondarily associated as univalents (Person, 1955 Riley and Chapman, 1957). Occasionally the secondarily associated univalents then orientate on the first metaphase plate and separate one to each pole in late anaphase.…”
Section: Meiotic Behaviourmentioning
confidence: 99%
“…The 2 meiotic stages, metaphase I and anaphase I, in such cases are indistinguishable as the univalent chromosomes remain scattered in the meiocytes. In such cases, the term meta-anaphase is used as coined by Person (1955). The spontaneous occurrence of such plants showing high frequency of univalent chromosomes and associated meiotic irregularities during male meiosis is already known in other plant species (Kaul andMurthy 1985, Singh 2002).…”
Section: Resultsmentioning
confidence: 99%
“…According to Levan (1942) nonhomologous pairing in haploid rye seems to start at the heterochromatic segments. Person (1955) reported e-e (end-to-end) and s-s (side_by-side) association of chromosome during meiosis in haploid Triticum aestivum. He suggested that homology is not a factor in the formation of e-e associations.…”
Section: Discussionmentioning
confidence: 99%
“…PAIRING between partner chromosomes is specific and depends on homology, while nonspecific pairing between nonhomologous regions is, in most cases, the result of heterochromatic fusion (Riley and Law, 1965;Riley and Chapman, 1957;Person, 1955). The introduction of a new, experimentallyinduced, heterochromatic chromosome into normal male plants of R. thyrsifiorus changes the pattern of sex chromosome pairing and cause conjugation between nonhomologous partners.…”
Section: Introductionmentioning
confidence: 99%